Diffusion Tensor Imaging in Cases with Visual Field Defect after Anterior Temporal Lobectomy - Taoka, Toshiaki; Sakamoto, Masahiko; Iwasaki, Satoru; Nakagawa, Hiroyuki; Fukusumi, Akio; Hirohashi, Shinji; Taoka, Keiko; Kichikawa, Kimihiko; Hoshida, Tohru; Sakaki, Toshisuke (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Visual defect due to optic radiation injury is a complication of temporal lobectomy for temporal epilepsy. To investigate whether diffusion tensor imaging can delineate the changes in optic radiations after lobectomy, we evaluated parameters on tensor images for optic radiations and correlated them with visual defect.METHODS: We examined 14 cases after temporal lobectomy. Durations after surgeries ranged from 3 weeks to 9 years. The cases were classified into three groups on the basis of the severity of visual field defect (A–C, with group C the most severe). We evaluated signals on T2-weighted images and parameters of tensor images, including fractional anisotropy (FA) and apparent diffusion coefficient (ADC), for the optic radiation in both the operated and intact side.RESULTS: On T2-weighted images, high signals in optic radiations were seen in four cases, occurring more than 4 weeks after surgery. The mean operated-to–intact side FA ratio in the optic radiation decreased according to severity of visual defect (group A, 0.88; group B, 0.89; group C, 0.73). The mean operated-to-intact side ADC ratio showed no significant difference in the overall cases. The ratio for ADC, however, tended to increase according to visual defect in cases after 10 weeks postsurgery.CONCLUSION: Optic radiation showed a decreased FA value in cases after temporal lobectomy. In later stages, ADC values tended to increase and high signal intensities on T2-weighted images were observed. The FA value can be used for evaluating Wallerian degeneration of optic radiation even in the early stages after surgery.